Islam in a More Conservative Western World (American Journal of Islam and Society, 1996)
My findings are tentative and subject to further research. This presentationrests on three paradoxes of great relevance to Muslims in the West.The first paradox is that, from the point of views of Muslims in the West,western secularism might be good news and western materialism might bebad news. In other words, western secularism is perhaps a blessing in disguisefor Muslims, whereas western materialism is a curse. The secondparadox is that recent Republican, rather than Democratic, foreign policyhas been more friendly to Muslims, wherea Democratic, rather thenRepublican, domestic policies are probably more friendly to Muslims. Thethird paradox concerns the two Islams in the United States: indigenou andimmigrant. In the United States, western secularism has protected minorityreligious groups by insisting on the separation of church and state. Thisis as major reason why American Jews have been among the greatestdefenders of the separation of church and state, for any breach could leadto the imposition of some practices of the religious majority, such as forcingJewish children to participate in Christian prayers at school.The secular state permits religious minorities to practice their religionsin relative peace. Of course, like all doctrines, secularism has its fanaticwho sometimes want to degrade, rather than protect, the sacred. But at itsbest, a secular state is a refuge of safety for minority religions. It is in thissense that western secularism is a friend of Muslims living in the West.But while secularism represents a divorce from formal religion, materialismis a dilution of spirituality. One can be without a formal religion andstill be deeply spiritual in a humanistic sense. John Stuart Mill and BertrandRussell, for example, had no formal religion, yet each had deeply spiritualvalues. Albert Schweitzer, the Nobel Laureate for Peace and an eventualagnostic, remained deeply committed to the principle of reverence for life,even to the extent of protecting the lives of insects in Africa ...